Digital Authoritarianism or Democratic Innovation? State Regulation of Social Media Platforms in Indonesia - Salma Nabila Prameswari (Indonesian Political Transformation, 2025)
Governments worldwide increasingly regulate digital platforms to combat misinformation, hate speech, and harmful online content. However, expanding regulatory authority also raises concerns regarding freedom of expression, democratic accountability, and state surveillance. Indonesia provides an important case for examining these competing dynamics because of its rapidly growing digital population and evolving regulatory framework governing social media platforms. This study explores whether Indonesia's digital governance reforms represent democratic innovation or a gradual movement toward digital authoritarianism. Using qualitative institutional analysis, the research examines legislation, judicial decisions, platform governance policies, and interviews with policymakers, civil society organizations, journalists, and technology experts. The findings indicate that Indonesia's regulatory approach reflects a hybrid governance model characterized by legitimate efforts to improve digital accountability alongside increasing concerns regarding discretionary enforcement, transparency, and protection of civil liberties. Rather than representing a binary choice between democracy and authoritarianism, Indonesia illustrates the complexities of governing digital spaces within emerging democracies facing competing demands for security, political stability, and digital rights. The article develops a conceptual framework explaining how regulatory legitimacy depends upon procedural transparency, institutional independence, proportional enforcement, and multi-stakeholder participation. The study contributes to comparative research on digital governance by providing evidence from the Global South, where institutional conditions differ significantly from Western democracies. The findings offer policy recommendations for designing balanced regulatory systems capable of addressing digital harms while preserving democratic freedoms and constitutional protections.